2016
DOI: 10.1371/journal.pone.0168262
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the State of Knowledge Regarding the Effectiveness of Interventions to Contain Pandemic Influenza Transmission: A Systematic Review and Narrative Synthesis

Abstract: BackgroundInfluenza pandemics occur when a novel influenza strain, to which humans are immunologically naïve, emerges to cause infection and illness on a global scale. Differences in the viral properties of pandemic strains, relative to seasonal ones, can alter the effectiveness of interventions typically implemented to control seasonal influenza burden. As a result, annual control activities may not be sufficient to contain an influenza pandemic.PurposeThis study seeks to inform pandemic policy and planning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…This previous review, which was based on 19 articles (five of these articles included workplace closure and two included workplace social distancing), concluded that combination strategies increased the effectiveness of individual strategies. Other systematic reviews that have assessed the effectiveness of interventions in reducing pandemic influenza transmission did not examine workplace social distancing measures [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This previous review, which was based on 19 articles (five of these articles included workplace closure and two included workplace social distancing), concluded that combination strategies increased the effectiveness of individual strategies. Other systematic reviews that have assessed the effectiveness of interventions in reducing pandemic influenza transmission did not examine workplace social distancing measures [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 Influenza pandemics remain the most likely pandemic threat, with very serious health and socioeconomic consequences. 33 The current review takes forward the work on the pandemic plans by describing the gaps, where the lessons learned 14,16,[18][19][20] from the influenza A (H1N1) pandemic in 2009 remain to be included in the plans. We realize that plans are continuously being revised.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, massive antiviral prophylaxis might be effective in containing a viral pandemic as in the use of neuraminidase inhibitors against influenza (Saunders-Hastings et al, 2016). A Cochrane Collaboration review found that prophylactic use of antiviral neuraminidase inhibitors reduce the risk of developing influenza (Jefferson et al, 2014).…”
Section: Antiviral Prophylaxis In Viral Epidemicsmentioning
confidence: 99%
“…Using influenza as a model for preventive management of respiratory viral pandemics, the key concerns are surges in community attack rates and healthcare system demand (Nap et al, 2007) , which in turn lead to disruptions in healthcare with potentially disastrous social and economic ramifications. In their systemic review and meta-analysis of effective interventions to contain an influenza pandemic, Saunders-Hastings et al identified vaccination and antiviral prophylaxis as two major pharmaceutical interventions that can be effective (Saunders-Hastings et al, 2016). However, to date we have neither developed a vaccine nor is there any approved or established antiviral prophylaxis in deployment against In the case of COVID-19, hiding in plain view is a plausible and potential prophylaxis option that can be relatively easily achievable by repositioning the old drug chloroquine (CQ), one of the most prescribed drugs in the world today (White et al, 2014).…”
Section: Introductionmentioning
confidence: 99%